Crime and Punishment: Is the existing offence for reckless breaches of health and safety duties working, or does New Zealand need something new? - Nicholson, Grant; Wray, Elizabeth (New Zealand Journal of Health and Safety Practice, 2024)
New Zealand law currently relies on proof of recklessness as the gateway standard for offences that can allow the Court to impose the highest financial and other penalties under the Health and Safety at Work Act 2015 (HSWA). Is the existing recklessness offence set out in section 47 of the HSWA fit-for-purpose, or would New Zealand be better served by adopting one (or both) of two available alternatives – a lower standard of gross negligence for conviction, or an additional new offence of corporate manslaughter with higher penalties in cases involving death?